Inuit involvement in developing a participatory action research project on youth, violence prevention, and health promotion - Morris, Marika (Études/Inuit/Studies, 2016)
This article describes the process of developing an academic and community participatory action research partnership on Inuit youth and violence prevention through social media. Pauktuutit Inuit Women of Canada chose the topic, defined the research goals, co-developed the first draft of the project and its methodology, established and chaired an Inuit advisory committee, spearheaded consultations with other Inuit organizations to refine the methodology, and co-facilitated a focus group. The “action” part of the project involved using the research results to develop with Inuit youth an outreach strategy to prevent violence and promote health via social media. The article discusses the research process, which was guided by Inuit Qaujimajatuqangit (traditional values) and which used a methodology redesigned by Inuit, including youth and elders. The result was a violence prevention focus group for Inuit aged 18 to 25, co-led by the Mamisarvik Healing Centre, and an online survey of social media use among Inuit aged 18 to 25. This participatory action research process is presented as a potential model for academic-community partnerships.